Ethical understandings of proxy decision making for research involving adults lacking capacity: A systematic review (framework synthesis) of empirical research. Issue 4 (2nd October 2018) - Shepherd, Victoria; Hood, Kerenza; Sheehan, Mark; Griffith, Richard; Jordan, Amber; Wood, Fiona
Abstract: Background: Research involving adults lacking mental capacity relies on the involvement of a proxy or surrogate, although this raises a number of ethical concerns. Empirical studies have examined attitudes towards proxy decision-making, proxies' authority as decision-makers, decision accuracy, and other relevant factors. However, a comprehensive evidence-based account of proxy decision-making is lacking. This systematic review provides a synthesis of the empirical data reporting the ethical issues surrounding decisions made by research proxies, and the development of a conceptual framework of proxy decision-making for research.Methods: A systematic review was conducted according to PRISMA guidelines. Databases including MEDLINE, EMBASE, and CINAHL were searched using a combination of search terms, and empirical data from eligible studies were retrieved. The review followed the framework synthesis approach to refine and develop a conceptual framework.Results: Thirty-four studies were included in the review. Two dimensions of proxy decision-making emerged. The ethical framing criteria of decision-making used by proxies: use of a substituted judgement, use of a best interests approach, combination of substituted judgement and best interests, and 'something else', and the active elements of proxy decision-making: 'knowing the person', patient-proxy relationship, accuracy of the decision, and balancing risks, benefits and burdens, and attitudes towards proxy decision-making. Interactions between the framing criteria and the elements of decision-making are complex and contextually-situated.Conclusions: The findings from this systematic review challenge the accepted reductionist account of proxy decision-making. Decision-making by research proxies is highly contextualized and multifactorial in nature. The choice of proxy and the relational features of decision-making play a fundamental role: both in providing the proxy's authority as decision-maker, and guiding the decision-making process. The conceptual framework describes the relationship between the framing criteria used by the proxy, and the active elements of decision-making. Further work to develop, and empirically test the proposed framework is needed.